Weak cosmic censorship and the rotating quantum BTZ black hole - Frassino, A. M.; Rocha, J. V.; Sanna, A. P. (Journal of High Energy Physics, 2024)
Tests of the weak cosmic censorship conjecture examine the possibility of the breakdown of predictivity of the gravitational theory considered, by checking if curvature singularities typically present in black hole spacetimes are concealed within an event horizon at all times. A possible method to perform such tests was proposed by Wald and consists in trying to overspin an extremal rotating black hole by throwing at it a test particle with large angular momentum. In this paper, we analyze the effects of dropping a test particle into an extremal quantum rotating BTZ black hole, whose three-dimensional metric captures the exact backreaction from strongly coupled quantum conformal fields. Our analysis reveals that, despite the inclusion of quantum effects, and akin to the classical scenario, these attempts to destroy the black hole are doomed to be unsuccessful. Particles carrying the maximum angular momentum and still falling into an extremal quantum BTZ black hole can, at most, leave it extremal. Nevertheless, we found numerical evidence that large backreaction of the quantum fields tends to disfavor violations of cosmic censorship.